Rising to climate challenges and opportunities in managing Lincolnshire's coastline, UK. Issue 5 (March 2021) - Rouse, Andrew; Campbell, Deborah; Scott, Angela; Hunt, Paul; Trewhella, Steven; Hesk, Paul
Abstract : The UK's largest and longest running coastal defence scheme reduces the coastal flood risk to 40% of Lincolnshire. A concrete seawall, sand dunes and beach frontage provide the primary protection to 45 000 properties across 35 000 ha. Annual beach nourishment sustains the standard of protection, but the cost and carbon dioxide emissions of the sediment volumes required will increase with climate change. This paper describes a new approach adopted in 2019, which involves working with local authorities and other stakeholders to realise a wider range of social, environmental, commercial and infrastructure benefits. Opportunities to achieve a target of net zero carbon dioxide emissions and reduce other causes of climate change are also discussed.